Nutritional status of the potted chrysanthemum relative to electrical conductivity and salt leaching - Beckmann-Cavalcante, Márkilla Zunete (2013)
The quality of ornamental plants grown in pots is highly dependent on fertilization and substrate management. To this effect, we carried out an experiment in a protected environment to evaluate the nutritional status of the chrysanthemum cv. Miramar grown in pots, relative to the electrical conductivity of the nutrient solution and the leaching of salts. The experimental design was of randomized blocks with four replications and the treatments arranged in a 5 × 2 factorial, relating to the levels of electrical conductivity of the nutrient solution (ECs = 2.1; 2.8; 3.5; 4.2 and 4.9 dS m-1) in substrates without (SNL) and with (SWL) washing for the leaching of salts. The nutritional status of the plants was evaluated by leaf analysis of macronutrients (N, P, K, Ca, Mg and S) and micronutrients (Cu, Fe, Mn and Zn). The increase in ECs inhibited the accumulation of micronutrients and of nitrogen, but stimulated the levels of P, K, Ca, Mg and S in the leaf dry mass of the chrysanthemum. The leaching of salts increased the concentration Cu, Fe and Mn in the plant leaves. Among the macronutrients, with the except of calcium and sulphur, no significant difference was observed for N, P, K and Mg relative to the leaching of salts.